An observational study of the lung clearance index throughout childhood in cystic fibrosis: early years matter. Issue 4 (1st October 2020) - Davies, Gwyneth; Stanojevic, Sanja; Raywood, Emma; Duncan, Julie A.; Stocks, Janet; Lum, Sooky; Bush, Andrew; Viviani, Laura; Wade, Angie; Calder, Alistair; Owens, Catherine M.; Goubau, Christophe; et al.
The London Cystic Fibrosis Collaboration (LCFC) has prospectively followed a clinically diagnosed cohort of infants with cystic fibrosis (CF) born in South East England since 1999 [1–4]. Over the past 20 years, the LCFC has obtained comprehensive measures of lung function and structure, including measures of ventilation inhomogeneity (lung clearance index (LCI)) and high-resolution computed tomography (HRCT) scans. By pre-school age, 73% of this cohort had LCI above the limits of normal, compared with 7% with abnormal forced expiratory volume in 0.5 seconds (FEV0.5 ) [1]. Children with elevated LCI during pre-school years also had worse lung function at early school age [2]. The aim of this study was to investigate how LCI changes across childhood to better understand to what extent LCI results at pre-school age are an indicator of lung disease severity in adolescence. Lung clearance index (LCI) in the early years was associated with LCI during adolescence in children with cystic fibrosis. Pre-school LCI may help to identify children in whom treatment could be intensified. https://bit.ly/2yKyMbM